Targeting Investigation and Treatment in Type 2 Myocardial Infarction - Caelan Taggart, MD; Amy Ferry, BSc; Stephanie Barker, BSc; Kelly Williams, BSc; Grace Souter, BSc; Anda Bularga, MD; Ryan Wereski, MD; Michael J. McDermott, MD; Michelle C. Williams, MD, PhD; Jasper Boeddinghaus, MD; Christopher White, BSc; Jagdeep S. Singh, MD; et al. (JACC: Advances)
Background: Type 2 myocardial infarction occurs in the absence of atherothrombosis, due to myocardial oxygen supply or demand imbalance, often during another acute illness. It is common and associated with poor clinical outcomes. No randomized controlled trials are available to guide investigation or treatment. Objectives: The authors assessed the feasibility of implementing a complex intervention of investigation and treatment for coronary and structural heart disease in patients with type 2 myocardial infarction. Methods: A pilot phase of a prospective randomized controlled trial was conducted. Process outcomes included the proportion of eligible patients approached, consented, and randomized. Adherence was defined as the number of recommended investigations and treatments administered at 90 days. Qualitative interviews explored reasons for participation and patient experience. Results: Between November 2022 and November 2023, 4,127 patients with increased cardiac troponin concentrations were screened across 3 sites, and 403 patients (10%) met inclusion criteria. One hundred and forty-three patients (35%) were eligible, 119 patients (83%) were approached, and 60 patients (42%, age 70 ± 10 years, 38% women) consented and randomized to the intervention (n = 28) or standard care (n = 32). Follow-up was complete in all participants. Adherence to recommendations was 90.7% (95% CI: 85.3%-96.1%). Patients highlighted variation in communication of the diagnosis and in trial investigation and management recommendations were potential barriers to participation. Conclusions: It is feasible to recruit and randomize patients with type 2 myocardial infarction to a complex intervention targeting coronary or structural heart disease. A multicenter trial with an optimized intervention is now required to inform practice.